ANALISIS FAKTOR MEMPENGARUHI NILAI TUKAR PETANI PADI GABAH KERING GILING DI KECAMATAN TANAH ABANG KABUPATEN PENUKAL ABAB LEMATANG ILIR - Astuti, Widia; Purba, Yudhi Zuriah Wirya; Thanomutiara, Eka (Fakultas Pertanian Universitas Mataram, 2024)
The research aims to analyze what factors influence the Farmer's Exchange Rate. This research will be carried out from June to July 2024. The data used in this research is primary data taken using the survey method. Sampling used the proportional stratified random sampling method with a sample size of 35 sample farmers from 175 population members in Sedupi Village and 176 population members in Raja Barat Village. The research results show that collectively the factors that influence the Farmer's Exchange Rate (NTP) are rice income (I), basic price of grain (HDG), rice production costs (B) and household expenditure (P). Partially, the factor that has the most significantly positive influence on NTP is income, while the factors that do not have a significantly negative influence are production costs and expenses of farming families. Meanwhile, the basic price of grain has no effect on the Farmers' Exchange Rate.